Citocalasinas produzidas por Xylaria sp., um fungo endofítico de Piper aduncum (piperaceae) - Silva, Geraldo H. [UNESP] (2010)
A chemical study on the EtOAc extract produced by Xylaria sp., an endophytic fungus from Piper aduncum, resulted in the isolation of a new cytochalasin 1, along with five known 19,20-epoxycytochalasin D (2), C (3), N (4), Q (5), and R (6). The 1-6 were evaluated against the fungi C. cladosporioides and C. sphaerospermum and only 5 showed weak activity. The cytotoxicity in vitro against HeLA and CHO cells lines were investigated and the cytochalasins 2-4, and 6 showed a strong activity against HeLA. The DNAdamaging activity of 1-6 were also investigated against mutant strains of S. cerevisiae.